2014
DOI: 10.3390/toxins6082541
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Venom’s Toxin-Neutralizing Antibody Fragments and Its Therapeutic Potential

Abstract: Serum therapy remains the only specific treatment against envenoming, but anti-venoms are still prepared by fragmentation of polyclonal antibodies isolated from hyper-immunized horse serum. Most of these anti-venoms are considered to be efficient, but their production is tedious, and their use may be associated with adverse effects. Recombinant antibodies and smaller functional units are now emerging as credible alternatives and constitute a source of still unexploited biomolecules capable of neutralizing veno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(21 citation statements)
references
References 97 publications
1
18
0
Order By: Relevance
“…Neutralizing equine botulinum antitoxin is primarily composed of IgG T , a highly glycosylated IgG that is particularly immunogenic in humans [23,24]. Studies of equine antisera to venoms have shown that no more than 20% of equine antibodies in antitoxin are directed specifically against the target toxin, whereas <5% are neutralizing antibodies, some with overlapping neutralizing epitopes with different affinities [25]. This combination leads to a low activity-to-volume ratio, requiring higher doses [25].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Neutralizing equine botulinum antitoxin is primarily composed of IgG T , a highly glycosylated IgG that is particularly immunogenic in humans [23,24]. Studies of equine antisera to venoms have shown that no more than 20% of equine antibodies in antitoxin are directed specifically against the target toxin, whereas <5% are neutralizing antibodies, some with overlapping neutralizing epitopes with different affinities [25]. This combination leads to a low activity-to-volume ratio, requiring higher doses [25].…”
Section: Discussionmentioning
confidence: 99%
“…Studies of equine antisera to venoms have shown that no more than 20% of equine antibodies in antitoxin are directed specifically against the target toxin, whereas <5% are neutralizing antibodies, some with overlapping neutralizing epitopes with different affinities [25]. This combination leads to a low activity-to-volume ratio, requiring higher doses [25]. The percentage of neutralizing antibody produced by the same mechanism to botulinum is likely similar.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Many of these components have been found with the unique properties to circumvent the global therapeutic challenges. 18 Venoms and purified toxins of scorpion, such as chlorotoxin (a 36-amino acid peptide), are effective inhibitors of glioma cells. A synthetic peptide from chlorotoxin (TM-601) has the capability to cross the blood-brain barrier, and it is also used in clinical trials for treating glioma.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the cost of pharmaceutical development has dramatically decreased making possible to consider the rise of recombinant antibodies for the treatment of orphan and rare diseases [7]. In the mean time, a considered number of early preclinical studies have clearly demonstrated the potential of anti-toxins recombinant antibody fragments for a "targeted" therapy toward the treatment envenomings, with improved efficacy and safety [8][9][10].…”
Section: Introductionmentioning
confidence: 99%